2003
DOI: 10.1111/j.1553-2712.2003.tb00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of Criteria Used in Assessing Blunt Head Injury Patients for Intracranial Injuries

Abstract: The clinicians in our study had a substantial level of agreement regarding most clinical criteria assessed in this large sample of patients with blunt head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The κ statistics for agreement between blinded and unblinded reviews were 0.80 for chest pain, 0.85 for heart failure, 0.86 for coronary revascularization and 0.74 for myocardial infarction (Table 2). Thus, the agreement between the blinded and unblinded reviews was in the good to excellent range for all outcomes [17, 18]. The standard errors for these κ statistics were near 0.06 for all, and p-values were all < 0.0001 (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…The κ statistics for agreement between blinded and unblinded reviews were 0.80 for chest pain, 0.85 for heart failure, 0.86 for coronary revascularization and 0.74 for myocardial infarction (Table 2). Thus, the agreement between the blinded and unblinded reviews was in the good to excellent range for all outcomes [17, 18]. The standard errors for these κ statistics were near 0.06 for all, and p-values were all < 0.0001 (Table 2).…”
Section: Resultsmentioning
confidence: 92%
“…Altered mental status, specifically as assessed by the GCS and other rating scales, has been most extensively studied, although much of the published work is in adult patients, 16,17 or in patients with conditions other than acute head injury. 18,19 In a study of children with minor head injury (defined as at nine Canadian pediatric teaching hospitals, Osmond et al 20 found moderate agreement in initial GCS, with j = 0.54.…”
Section: Discussionmentioning
confidence: 99%
“…All 7 criteria are basic elements of a history and physical examination and have demonstrated high interrater reliability. 31 Although the test characteristics of the decision aid suggest that it could be useful in clinical practice, it is important to note that this is a derivation study only and must be validated in a separate cohort before it can be recommended for widespread adoption. In addition, among the subset of patients who were younger than 3 years, for whom the sample size is small, the CIs for sensitivity and NPV are wide, making additional prospective validation in a larger cohort even more crucial.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 These candidate variables were chosen by consensus of the study investigators because they had been described as possibly being predictive of ICI in previous literature,* and each of them was shown during the derivation study to exhibit a high level of raw agreement, as well as a Ͼ 0.50. 31 The optimum decision instrument derived for the entire study cohort of 13 728 patients is composed of the following 8 variables: evidence of significant skull fracture, altered level of alertness, neurologic deficit, persistent vomiting, presence of scalp hematoma, abnormal behavior, coagulopathy, and age Ͼ65 years. 26 This instrument had a sensitivity of 98.3% (95% CI: 97.2-99.0) and a specificity of 13.7% (95% CI: 13.1-14.3) in all study patients.…”
Section: Methodsmentioning
confidence: 99%